2019
DOI: 10.1002/pmic.201900055
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Phosphorylation Landscape of Mouse Spermatids during Spermiogenesis

Abstract: The characteristic tadpole shape of sperm is formed from round spermatids via spermiogenesis, a process which results in dramatic morphological changes in the final stage of spermatogenesis in the testis. Protein phosphorylation, as one of the most important post-translational modifications, can regulate spermiogenesis; however, the phosphorylation events taking place during this process have not been systematically analyzed. In order to better understand the role of phosphorylation in spermiogenesis, large-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
(19 reference statements)
1
13
0
Order By: Relevance
“…Spermatid differentiation is a complex process closely associated with phosphorylation that results in dramatic morphological and functional changes in spermatids. 44,45 Consistent with the localization characteristics of CDK7 (expressed in steps 1-11 of spermatids) (Figure 1b), our results suggested that the inhibition of CDK7 affects spermatid differentiation, resulting in the observed reduced in sperm count and quality. On the one hand, inhibition of CDK7 affected acrosome formation and nuclear condensation and structure, leading to sperm head malformation (Figure 5).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Spermatid differentiation is a complex process closely associated with phosphorylation that results in dramatic morphological and functional changes in spermatids. 44,45 Consistent with the localization characteristics of CDK7 (expressed in steps 1-11 of spermatids) (Figure 1b), our results suggested that the inhibition of CDK7 affects spermatid differentiation, resulting in the observed reduced in sperm count and quality. On the one hand, inhibition of CDK7 affected acrosome formation and nuclear condensation and structure, leading to sperm head malformation (Figure 5).…”
Section: Discussionsupporting
confidence: 87%
“…Phosphorylation is particularly active during spermiogenesis 44 . We previously constructed the phosphoproteome of mouse spermatids 45 . Based on bioinformatics analysis, we predicted the potential phosphorylated target proteins downstream of CDK7 (Figure 8a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple protein post-translational modifications (PTMs) occur in germ cells during spermatogenesis, such as acetylation [2,3], crotonylation [4], glycosylation [5][6][7], phosphorylation [8][9][10], SUMOylation [11], and ubiquitination [12]. Many of these PTMs have been identified to play important roles in sustaining mammalian spermatogenesis and male fertility [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Ohno et al investigated the ZDHHCs genes expression patterns in human by RT-PCR, and classified ZDHHC genes into roughly three groups according to their tissue-specific expression patterns: highly ubiquitous, nearly ubiquitous, and tissue-specific [27]. The highly ubiquitous and nearly ubiquitous groups each include most of ZDHHC genes (ZDHHC4, 5,7,8,10,12,13,17,and 22;and ZDHHC1,3,6,9,14,16,18, and 21, respectively), indicating that multiple ZDHHC proteins are co-expressed in the same cell. Interestingly, a small number of ZDHHC genes are tissue-specific, including ZDHHC2, 11, 15, 19, and 20.…”
Section: Introductionmentioning
confidence: 99%